Identity and frequency of non-traditional companion animals presented at a university teaching hospital: a retrospective study (2009–2019). - Ángeles-Torres, Luis Enrique; Ducoing-Watty, Adriana Margarita; Silva-Castillo, Rene O; Villavicencio-Oropeza, Amalia; Maldonado-Reséndiz, Ricardo Itzcoatl (Veterinaria México OA, 2023)
This study describes the diversity of the species received for medical evaluation at the Exotic Pet and Wildlife Teaching Hospital in Mexico; identifying the most common non-traditional companion animals owned, the frequency of the species received along the years, and which of those correspond to native Mexican wildlife. This retrospective descriptive study comprised 8 619 patient records from 2009 to 2019. During the period analyzed, 129 species were identified, 60 of these being native Mexican wildlife. Most of the patients received were mammals (56.36 %) followed by reptiles (38.73 %), and 4.91 % remaining were composed by birds, amphibian, fish and invertebrate species. Eight species contributed to the highest percentage of the records (79.88 %), being the red-eared slider (Trachemys scripta elegans) the most common (18.71 %). The number of annual records varied through the period with a trend for increased demand recently. It was possible to identify changes in the frequency of visits of different species over the study period, which allowed us to determine that the preference for the maintenance of some species in captivity has decreased. Commonly received species identification allows veterinary medicine students to specialize and develop the required species-specific medical competencies.